Impact of Remittanceson Poverty and Financial Development in Sub-Saharan Africa - Gupta, Sanjeev (International Monetary Fund, 2007)
This paper assesses the impact of the steadily growing remittance flows to sub-Saharan Africa (SSA). Though the region receives only a small portion of the total recorded remittances to developing countries, and the volume of aid flows to SSA swamps remittances, this paper finds that remittances, which are a stable, private transfer, have a direct poverty mitigating effect, and promote financial development. These findings hold even after factoring in the reverse causality between remittances, poverty and financial development. The paper posits that formalizing such flows can serve as an effective access point for ""unbanked"" individuals and households, and that the effective use of such flows can mitigate the costs of skilled out-migration in SSA